Effect of water absorption on the mechanical properties of cross-ply hybrid pseudo- stem banana/glass fibre reinforced polypropylene composite - Dhar Malingam, Sivakumar; Zulkafli, Norizzati; Sheikh Md Fadzullah, Siti Hajar; Zakaria, Kamarul Ariffin; Mustafa, Zaleha; Subramonian, Sivarao (Institute of Physics Publishing Ltd., 2019)
The initiative to reduce the consumption of non-renewable resources increases the awareness of being green in composites. The synthetic fibres are currently substituted by natural fibres applicable in various industries such as automotive and building. In this study, the effects of water absorption on the tensile and flexural properties of cross-ply hybrid pseudo-stem banana/glass fibre reinforced polypropylene composites are investigated. The hybrid banana (B)/glass(G) polypropylene composites and the reference specimens of the non-hybrid composites of the plain banana and glass fibres termed the BBB and GGG specimens were fabricated using hot compression moulding method. Water absorption test was conducted according to ASTM D570 until the specimens reached saturation. Tensile (ASTM D3039) and flexural (ASTM D790)test were carried out on the dry specimens as well as the wetted specimens. It can be observed that non-hybrid GGG has the best water absorption properties and hybrid specimen with glass as outermost skin shows a comparable result. However, water absorption reduced the mechanical properties of the composites. The incorporation of glass fibre in the composites improved overall properties of the composites. The hybrid GBG dry specimen tensile strength and wet specimen flexural strength is 136.28 and 73.86 MPa respectively. The hybrid composite GBG shows comparable flexural properties to GGG composite.